The Influence of Cooperative Learningonsocialskills in Graduate Students in Inclusionschools - Maulidia, Fara Varistin; Ayun, Safitri qurrata; Husna, Amaliya Syahida Hilyatul; Widyasti, ZanifatusArdila; Pradipta, Rizqi Fajar (Proceedings Series of Educational Studies, 2024)
Mental retardation is a condition where an individual has a level of intelligence far belowaverage, which is characterized by decreased intellectual abilities and difficulty incommunicating. These intellectual limitations affect an individual's ability to complete dailytasks, interact socially, and communicate with other people. Therefore, it is necessary to applyan interesting and interactive learning model to help children improve their social relationshipswith peers. The aim of this research is to identify the effect of cooperative learning typeNumbered Head Together (NHT) on improving the social skills of students with intellectual disabilities, especially in relationships with peers. Thus, it can be concluded whether theapplication of cooperative learning type Numbered Head Together (NHT) significantly hasapositive impact on the development of social skills of students with intellectual disabilitiesinrelationships with peers. This research uses a quantitative approach with a single subject research method using the A-B-A' pattern. The analytical methods used include analysis withinconditions and analysis between conditions. The measurement results in this study showedanincrease in the mean level at baseline-1 (A1) with a percentage of 40.62%. This percentage thenincreased in the intervention phase (B) to 67.5%. Furthermore, at baseline-2 (A2), there wasafurther increase until it reached 87.5%. In this study, the data overlap between baseline-1 (A1) and the intervention phase (B) was 0%. Therefore, it can be concluded that the applicationof cooperative learning type Numbered Heads Together (NHT) has a positive influence onthesocial skills of mentally retarded students in relationships with peers. The improvements that occur in relationships with peers include appreciating peers, interacting with peers, workingtogether in groups, and acceptance by peers. Keywords: Mentally disabled; Cooperative Learning; Social Skills